Identification of TSGA10 and GGNBP2 splicing variants in 5′ untranslated region with distinct expression profiles in brain tumor samples - Kazerani, Reihane; Salehipour, Pouya; Shah Mohammadi, Mohammadreza; Amanzadeh Jajin, Elnaz; Modarressi, Mohammad Hossein (Frontiers in Oncology, 2023)
Introduction Brain tumors (BTs) are perceived as one of the most common malignancies among children. The specific regulation of each gene can play a critical role in cancer progression. The present study aimed to determine the transcripts of the TSGA10 and GGNBP2 genes considering the alternative 5′UTR region and investigate the expression of these different transcripts in BTs. Material and methods The public data of brain tumor microarray datasets in GEO was employed to be analyzed with R software in order to evaluate the expression levels of TSGA10 and GGNBP2 genes (the Pheatmap package in R was also used to plot DEGs in a heat map). In addition, to validate our in-silico data analysis, RT-PCR was performed to determine the splicing variants of TSGA10 and GGNBP2 genes in testis and brain tumor samples. The expression levels of splice variants of these genes were analyzed in 30 brain tumor samples and two testicular tissue samples as a positive control. Results In silico results show that the differential expression levels of TSGA10 and GGNBP2 were significant in the GEO datasets of BTs compared to normal samples (with adjusted p-value<0.05 and log fold change > 1). In this study's experimental results, the TSGA10 gene produces four different transcripts with two distinct promoter regions and splicing exon 4. The results showed that the relative mRNA expression of transcripts without exon 4 was higher than transcripts with exon 4 in BT samples (p-value<001). In GGNBP2, exon 2 in the 5′UTR region and exon 6 in the coding sequence were spliced. The expression analysis results showed that the relative mRNA expression of transcript variants without exon 2 was higher than other transcript variants with exon 2 in BT samples (p-value<001). Conclusion The decreased expression levels of transcripts with longer 5′UTR in BT samples than in testicular or low-grade brain tumor samples may decrease their translation efficiency. Therefore, decreased amounts of TSGA10 and GGNBP2 as potential tumor suppressor proteins, especially in high-grade brain tumors, may cause cancer development by angiogenesis and metastasis.